Staged-release problem-based learning revitalizes medical students' intrinsic motivation and clinical reasoning. - Elhassan, Yasir Hassan; Sieben, Judith M.; Köhler, S. Eleonore; Brinke, Desirée Joosten-ten; Dolmans, Diana H. J. M. (Medical Teacher, 2026)
Introduction: Problem-based learning (PBL) is central to many curricula, yet reports of 'PBL fatigue' and inconsistent gains in clinical reasoning suggest room for improvement. Grounded in Self-Determination Theory, we designed a Staged-Release Model (SRM) to enhance students' intrinsic motivation and refine clinical reasoning. This study evaluated the SRM's initial implementation by examining its association with medical students' intrinsic motivation and perceived clinical reasoning ability. Methods: A mixed-methods study was conducted at the College of Medicine, Taibah University, Saudi Arabia. Third-year medical students (N = 151) participated in the new 7-step model (SRM). Quantitative data were collected using the 24-item Basic Psychological Needs Satisfaction and Frustration Scale (BPNSFS), which assessed, on a 5-point Likert scale, students' basic needs for intrinsic motivation. Qualitative data were collected through semi-structured focus group interviews. Results: Median scores for satisfaction with autonomy, relatedness, and competence were positive, accompanied by very low frustration scores. Qualitative analysis suggested that using the model enhanced students' learning of clinical reasoning, provided effective group interaction and engagement in the clinical context, and offered suggestions for improving consolidation sessions and tutor facilitation. Disscussion: This study suggests that SRM may enhance students' intrinsic motivation, potentially alleviating PBL fatigue, and may support the development of clinical reasoning by meeting students' basic psychological needs.